Impact of vacuum clamping system designs on surface quality during the end milling process - Ab Wahab, Norfariza; Abu Bakar, Nur Adlin; Nassiruddin, Muhammad Amirul Adli; Yaakob, Mohd Yuhazri; Abu Bakar, Mohd Hadzley; Mohd Sani, Muhamad Akmal; Rahman, Irfan Ur (Microscopy Society of Malaysia, 2024)
Traditional clamping systems often face challenges when securing thin materials, risking damage to the workpiece due to excessive force. In mass production, consistent and smooth processes are essential. Conventional clamping methods, such as top or side clamping, may interfere with the cutting tool's path or require additional safety measures. This study explores the application of a hybrid vacuum clamping system designed to securely hold acrylic plates during machining, focusing on depth and surface image analysis. A custom-designed vacuum block, available in two configurations—support airway and flat airway—was used to clamp a 160 × 160 × 6 mm acrylic plate. End milling with a 2 mm depth of cut (DOC) was performed, repeating the horizontal tool path seven times under varying pressure settings (-85 kPa to-25 kPa). Depth analysis was conducted using a Coordinate Measuring Machine (CMM), while surface images were captured via optical microscope. The findings indicate that the support block design provided better depth accuracy and surface quality, particularly at lower pressure settings, compared to the flat airway design. The results suggest that optimizing pressure settings and vacuum block design can enhance machining precision and workpiece surface integrity in thin material applications. A microscopic examination of the surface revealed that the vacuum clamping system effectively secured a 6 mm thick acrylic plate during the end milling process, at a pressure setting ranging from-85 to-45 kPa. This study provides valuable insights into improving vacuum clamping systems for efficient and accurate machining processes.